Michała Walickiego i Juliusza Starzyńskiego „Dzieje sztuki polskiej” w II Rzeczypospolitej. Zachód, Polska, Wschód - Labuda, Adam S. (Artium Quaestiones, 2019)
Writing an academic history of Polish art was an urgent task of art historians after World War I, when the country regained its political independence. An important and creditable achievement in that respect was a study by Michał Walicki and Juliusz Starzyński, published in 1934 as a kind of supplement to the monumental Geschichte der Kunst von der altchristlichen Zeit bis zur Gegenwart by the Marburg historian Richard Hamann, translated at that time into Polish. In 1936, the work of the Polish scholars was published again in the form of a separate book. The paper focuses on three problems that were addressed in it: the cultural and artistic ties of Poland to the West, the vernacular features of Polish art, and the presence of the “Eastern art” in Polish artistic heritage. The author examines also the question whether those issues were related to the political, social, and cultural reality of the Second Polish Republic.